2021
DOI: 10.1038/s41598-021-03138-6
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of TyG index distribution and its relationship to cardiometabolic risk factors in children and adolescents

Abstract: The purpose of this study was to present age- and sex-specific distributions of the triglyceride-glucose (TyG) index and to evaluate their relationship with cardiometabolic risk factors in children and adolescents. A total of 7404 participants aged 10–18 years from the Korean National Health and Nutrition Survey were included as the reference population. The TyG index was calculated as ln(fasting triglyceride [mg/dL] × fasting glucose [mg/dL]/2). The percentile of the TyG index exhibited a steady linear relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The TyG index is associated with insulin resistance and dyslipidemia and has been recommended as a good indicator of the presence of cardiometabolic risk factors, particularly insulin sensitivity [ 11 , 18 , 34 , 35 ]. Besides, it has been reported that the TyG index has a high sensitivity for MetS in children and adolescents with obesity [ 11 , 19 , 36 ]. Similar to our result, Brito et al [ 20 ] reported in a systematic review that in the ROC curve analyses performed to predict the cardiometabolic risk factors, the TyG index threshold values ranged from 4.65 to 8.66, and the cut-off point in girls was higher than in boys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TyG index is associated with insulin resistance and dyslipidemia and has been recommended as a good indicator of the presence of cardiometabolic risk factors, particularly insulin sensitivity [ 11 , 18 , 34 , 35 ]. Besides, it has been reported that the TyG index has a high sensitivity for MetS in children and adolescents with obesity [ 11 , 19 , 36 ]. Similar to our result, Brito et al [ 20 ] reported in a systematic review that in the ROC curve analyses performed to predict the cardiometabolic risk factors, the TyG index threshold values ranged from 4.65 to 8.66, and the cut-off point in girls was higher than in boys.…”
Section: Discussionmentioning
confidence: 99%
“…All these findings explain why HOMA-IR levels and cut-off values for MetS are different in boys and girls with obesity. Another disadvantage of HOMA-IR is its limited usage due to cost, requiring standardization for insulin, a labile hormone [19,34]. It was shown that the difference in insulin sensitivity in children with obesity between the sexes is due to phenotypic characteristics, that there may be a gene responsible for it, and that girls have higher insulin resistance [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MetS is a research point of interest for several years as it affects more than 25% of the total adult population in the world due to its direct relation to CVDs [ 10 ]. This study was the first in Saudi Arabia to investigate the susceptibility of CVDs in different populations, depending on the cardiometabolic risk factors in the MetS’-related criteria: dyslipidemia, diabetes/insulin resistance, hypertension, anemia, hypothyroidism, hypovitaminosis-D, and creatinemia, and clarifies the prevalence of MetS/CVDs in either sex before and after the age of 40 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the primary surrogate marker to evaluate IR is homeostasis model assessment of IR (HOMA-IR) 9 . However, not only various physiological characteristics during puberty 10 , 11 , but the big change of basic characteristics like BMI 12 at puberty make it hard to evaluate IR in children and adolescents. The triglyceride-glucose index (TyG index), easily calculated using fasting plasma glucose (FPG) and triglyceride (TG) levels, has been regarded as an alternative surrogate marker for appraising IR, and the accuracy of TyG index to diagnose the IR was consistent with that of HOMA-IR 14 .…”
Section: Introductionmentioning
confidence: 99%